2021
DOI: 10.1038/s41598-021-94049-z
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effects of the combined Thai noni juice ethanolic extracts and 5-fluorouracil against cholangiocarcinoma cells in vitro and in vivo

Abstract: Application of 5-fluorouracil (5-FU) in cholangiocarcinoma (CCA) is limited by adverse side effects and chemoresistance. Therefore, the combination therapy of 5-FU with other substances, especially natural products may provide a new strategy for CCA treatment. The aim of this study was to evaluate the combination effects of 5-FU and two ethanolic extracts of Thai noni juice (TNJ) products on CCA cell lines and nude mice xenografts. The results of antiproliferative assay showed the combination treatment of 5-FU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Marmesinpossess multiple pharmacological functions including anti-inflammatory, antihepatotoxic and antitumor activities (63,64). Fluorouracil has anti-cancer effects (65). Moreover, we observed increased levels of L-palmitoylcarnitine, quinestrol, 7ketocholesterol, and tetrabromodiphenyl ether during thiram exposure.…”
Section: Discussionmentioning
confidence: 69%
“…Marmesinpossess multiple pharmacological functions including anti-inflammatory, antihepatotoxic and antitumor activities (63,64). Fluorouracil has anti-cancer effects (65). Moreover, we observed increased levels of L-palmitoylcarnitine, quinestrol, 7ketocholesterol, and tetrabromodiphenyl ether during thiram exposure.…”
Section: Discussionmentioning
confidence: 69%
“…It inhibited AGS cell proliferation with IC 50 of 35.59 µg/ml, which was only half the concentration required compared to the ethyl acetate extract of Celastrus orbiculatus (IC 50 68.24 mg/l or equivalent to 68.24 µg/ml) [ 71 ]. Previous research reported that the ethanolic extract of Thai noni juice Chiangrai ( Morinda citrifolia ) reduced viability KKU-213B cells with IC 50 values of 2.14 ± 0.08 mg/ml for 48 h, which was higher than 20-fold compared with ethyl acetate extract of Shorea roxburghii (91.60 µg/ml or equivalent to 0.09 mg/ml) [ 72 ]. After 48 h of treatment, ethyl acetate extract inhibited cell viability of HepG2 cells with IC 50 of 39.38 µg/ml, whereas other medicinal plant Thymus daenensis and Stachys pilifera showed higher IC 50 values of 210.2 ± 12 µg/ml and 109.7 ± 5 µg/ml, respectively [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…TNJ extracts reduced hepatotoxicity in vivo associated with FFU. The treatment in KKU 100 implanted nude mouse with the drug alone or in combination with a high dose of TNJ showed toxicity on mouse liver as compared to low doses of TNJ with the drug which showed no adverse effect on mouse spleen and kidney (Prompipak et al, 2021). The administration of TNJ, alone or combined with the anticancer drug doxorubicin, for 14 days to female Balb‐c mice inoculated with Ehrlich ascites tumor cells, was reported to reduce the size of tumors (about 40–50% smaller in the treated group compared to the control group).…”
Section: Synergistic Effects Of Bioactive Noni Compounds In Combinati...mentioning
confidence: 99%